THE OBJECTIVE OF THE NECESSITY OF ATTRACTING FOREIGN INVESTMENT TO THE ECONOMY OF UZBEKISTAN - Tugizova Malika Sokhib kizi, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
As it is known, in the case of any state, separated from the outside world, the world of science, science and technology from the field in the achievements of the economy of developed countries may not develop the effective use of experience. In the way of this goal is the active involvement of foreign investment to the national economy and plays an important role to increase the effectiveness of their use. However, the distribution of doing such a task, first and foremost, "foreign investment" the essence of the concept, characteristics, types and the means of obtaining clear and obvious role in the development of the economy, the necessity will arise.